Methods of valorization of natural resources. Part 2. Applications in the environmental impact assessment - Matyjasiak, Piotr (Studia Ecologiae et Bioethicae, 2012)
The aim of this paper is (i) to review the method of valorization of natural resources as applied in the environmental impact assessment, and (ii) to develop recommendations on how valorization expertise should be prepared in order to be comprehensive and transparent. Valorization is the proper time to carry out identification of the possible negative environmental impacts and damages of a planned project. It is recommended to perform valorization due to the state (numbers) and functions (quality) of natural resources. This approach is related to the concept of environmental damage, which is defined as a measurable adverse change in a natural resource or measurable impairment of a natural resource service (which means the functions performed by a natural resource for the benefit of another natural resource or the public). Valorization of natural resources should include an assessment of potential environmental damage, including an impact on the local biodiversity, the ecological connectivity, the N2000 network, and the legally protected areas. The valorization of natural resources should be performed at the following thematic levels focusing on the role of the area under consideration due to: (1) the implementation of the objectives of protection of Nature 2000 network and its overall coherence, (2) the implementation of the objectives of protection of legally protected areas other than N2000, (3) the maintenance of the ecological connectivity in a context other than the coherence of Nature 2000 network, (4) the maintenance of species and natural habitats with favorable conservation status, (5) the conservation of species and natural habitat types that are not legally protected.